PENYIDIKAN TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK OLEH DIREKTORAT RESESRSE KRIMINAL KHUSUS POLDA RIAU - Yogi Aditya Perdana; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Criminal acts constitute a criminal act that can be sentenced, any act that is threatened as a crime, a violation of either the Criminal Code or any other legislation. The defamation law or defamation through social media is a special criminal act whose legal sanction is regulated outside the Criminal Code, namely Law number 19 of 2016 regarding the amendment to Law Number 11 Year 2008 concerning Information and Electronic Transactions, as mentioned in Article 27 paragraph (3) stating: "Every person intentionally and without right to distribute and / or transmit and / or make accessible Electronic Information and / or Electronic Documents with defamatory and / or defamatory content. A person who is proven intentionally disseminating defamatory electronic information as meant in Article 27 paragraph (3) of Law Number 19 of 2016 concerning the amendment to Law Number 11 Year 2008 concerning Information and Electronic Transaction shall be charged with Article 45 Paragraph (1) of the ITE Law which states: Any Person who fulfills the elements as referred to in Article 27 paragraph (1), paragraph (2), paragraph (3), or paragraph (4) shall be punished with imprisonment for a maximum of 4 (six) years and / Or a fine of not more than Rp 650,000,000.00 (one billion rupiah). Problems and objectives to be discussed in this thesis is to know how the investigation of criminal defamation through online media conducted by the Directorate of Special Criminal Investigation Polda Riau.This type of research is sociological, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at the Directorate of Special Criminal Investigation of Riau Police, while the population and sample were all parties related to the problem studied in this study, data source used, primary data, secondary data and tertiary data, data collection techniques in this study with Interviews, questionnaires and literature studies.From the results of the study can be concluded that the investigation by the Directorate of Special Criminal Investigation Polda Riau as not yet carry out the task Maximum. Personnel, expert staff and special facilities devoted to the investigation and investigation process are inadequate. With the lack of personnel and facilities is causing it difficult to overcome cases of defamation through this online media. Suggestions for the Special Criminal Investigation Directorate to further enhance the addition of personnel, expert staff and facilities to facilitate the investigation and investigation process.Keywords: Investigation - Defamation - Online Media - Ditreskrimsus Polda Riau